2008
DOI: 10.1097/tp.0b013e318186f98a
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mycophenolate Mofetil Regimens for de Novo Renal Transplant Recipients: The Fixed-Dose Concentration-Controlled Trial

Abstract: There was no difference in the incidence of treatment failure between the concentration-controlled and the fixed-dose groups. The applied protocol of MMF dose adjustments based on target MPA exposure was not successful, partly because physicians seemed reluctant to implement substantial dose changes. Current initial MMF doses underexpose more than 35% of patients early after transplantation, increasing the risk for BPAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
224
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(238 citation statements)
references
References 21 publications
10
224
1
3
Order By: Relevance
“…Drug monitoring was never correlated with a lower incidence of therapy failure with mycophenolate mofetil, which was confirmed in a recent study. 16 However, so far, MPA monitoring was performed by measuring plasma concentrations, and pharmacogenetic factors such as polymorphisms were not considered. Thus, there is growing interest in the impact of genetic polymorphisms of drug-metabolizing enzymes and transporters on drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Drug monitoring was never correlated with a lower incidence of therapy failure with mycophenolate mofetil, which was confirmed in a recent study. 16 However, so far, MPA monitoring was performed by measuring plasma concentrations, and pharmacogenetic factors such as polymorphisms were not considered. Thus, there is growing interest in the impact of genetic polymorphisms of drug-metabolizing enzymes and transporters on drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mean MPA-AUC of CsAtreated patients on day 10 was 34.4 mg/h per L in the FixedDose Concentration-Controlled (FDCC) Study (13). The authors concluded that higher MPA dosages seemed to be necessary to reach early target AUC in CsA-treated populations (13).…”
Section: Discussionmentioning
confidence: 99%
“…Median MPA-AUC was only 33.7 mg/h per L on day 14 in the Apomygre study, and levels Ͼ40 mg/h per L were not achieved until month 1 using a concentration-controlled approach (12). Similarly, mean MPA-AUC of CsAtreated patients on day 10 was 34.4 mg/h per L in the FixedDose Concentration-Controlled (FDCC) Study (13). The authors concluded that higher MPA dosages seemed to be necessary to reach early target AUC in CsA-treated populations (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the present report was to evaluate whether taking the CYP3A4*22 allelic status into account affects the predictive value of the algorithm developed by Passey et al [3].The patients included in the present analysis were 185 de novo kidney transplant recipients treated with a tacrolimus-based regimen who participated in a trial comparing fixed-dose (FD) with concentration-controlled (CC) mycophenolate mofetil (MMF) treatment [4]. All patients had been previously genotyped for CYP3A4*22 and CYP3A5*3 alleles [1].…”
Section: Boxmentioning
confidence: 99%